2011
DOI: 10.1007/s10508-010-9722-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Masturbation in Healthy Sexual Development: Perceptions of Young Adults

Abstract: Despite efforts to identify masturbation as a strategy to improve sexual health, promote relational intimacy, and reduce unwanted pregnancy, STIs, and HIV transmission, masturbation as a context for healthy sexual development has been met with silence or trepidation in the scientific and educational communities. Relegated to the realm of commercial media, rather than rational discourse in families, schools, and the general public, young people receive mixed messages about this non-reproductive sexual behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 38 publications
4
92
0
5
Order By: Relevance
“…Some scholars suggested that reporting masturbation, particularly among women and adolescent men, may not be entirely honest due to the social pressure that study participants may feel when reporting sensitive sexual behaviors (Béjin, 1996;Halpern, Udry, Suchindran, & Campbell, 2000;Petersen & Hyde, 2010). Related to that, it has been argued that self-pleasuring among women remains a stigmatized activity that is often accompanied by feelings of shame and guilt-as demonstrated in recent U.S.-and UK-based qualitative research (Hogarth & Ingham, 2009;Kaestle & Allen, 2011). This may explain a relatively high proportion of missing responses (17%) to the question about frequency of masturbation observed in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars suggested that reporting masturbation, particularly among women and adolescent men, may not be entirely honest due to the social pressure that study participants may feel when reporting sensitive sexual behaviors (Béjin, 1996;Halpern, Udry, Suchindran, & Campbell, 2000;Petersen & Hyde, 2010). Related to that, it has been argued that self-pleasuring among women remains a stigmatized activity that is often accompanied by feelings of shame and guilt-as demonstrated in recent U.S.-and UK-based qualitative research (Hogarth & Ingham, 2009;Kaestle & Allen, 2011). This may explain a relatively high proportion of missing responses (17%) to the question about frequency of masturbation observed in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…As research results often point out the fact that attitudes toward sexuality are associated to sexual behavior (Lefkowitz et al, 2004;Luquis et al, 2012;Nikken & Graaf, 2013;Weeden & Sabini, 2007), solitary and dyadic sexual desires might be also related to specific sexual attitudes as well as to trajectories of partnerships. For instance, solitary sexual desire and activities are perceived as positive by some individuals, while for others, they are perceived as negative or even shameful sexual activities (Carvalheira & Leal, 2013;Costa, 2012;Davidson & Moore, 1994;Gerressu et al, 2008;Jaspard, 2005;Kaestle & Allen, 2011). Therefore, we expect that individuals who have developed intimate trajectories characterized by numerous partnerships facilitating permissive attitudes toward sexuality have greater solitary and dyadic desires, while those with few partnerships, which supposedly are associated with more conservative attitudes toward sexuality, might have lower solitary and dyadic desires.…”
Section: Intimate Trajectories and Sexualitymentioning
confidence: 99%
“…Fakat özellikle ergenlik çağlarında insan gelişimi-ne, vücut bütünü farkındalığına ve cinsel arzulanımlarda oto-kontrole destek sağlar. Bu nedenle, mastürbasyon açıkça cinsel sağlık için gereklidir, [2] öyle ki bazı cinsel terapilerde etkili olan bir tedavi şeklidir. [3] Bağımlılık veya sapkınlık olduğunu iddia edenler de yok değildir.…”
Section: Is the Definition Of Masturbation Clear Or Can It Change?unclassified